Orof acial Pain: Racial and Sex Differences Among Older Adults - Joseph L. Riley, 111, PhD; Gregg H. Gilbert, DDS, MBA; Marc W. Heft, DMD, PhD (Blackwell Synergy, 2002)
This study investigated racial differences in orofacial pain symptoms in a sample of older adults. Orofacial pain prevalence, persistence, severity, and behavioral impact were assessed. We also tested whether sex and race interact, such that racial differences are only observed fora single sex, or whether sex differences only occur within a single racial group